PID-sliding surface based sliding mode controller for anti-lock braking system of electric vehicle - Alkharasani, Batool Abdulsamad; Hassan, Mohd Khair; Akmeliawati, Rini; Zafira, Ribhan (American Scientific Publishers, 2016)
Anti-lock Braking System (ABS) is a crucial part in electric vehicle. It is an uncertain and nonlinear system. In this paper a Sliding Mode Control (SMC) technique with PID sliding surface is used to maintain the slip ratio, at 0.2 of ABS system. The mathematical representation of a quarter vehicle model that emphasizes essential characteristics of the whole vehicle was implemented in this research. The model was developed using Simulink and the proposed SMC technique was tested and validated. In addition, the sliding mode enforcement was ensured via stability analysis. The simulation results have shown good agreement and acceptable response of the ABS system